Keeping science's seat at the decision-making table: Mechanisms to motivate policy-makers to keep using scientific information in the age of disinformation - Justin N. Marleau; Kimberly D. Girling (Canadian Science Publishing, 2017)
Policy-makers are confronted with complex problems that require evaluating multiple streams of evidence and weighing competing interests to develop and implement solutions. However, the policy interventions available to resolve these problems have different levels of supporting scientific evidence. Decision-makers, who are not necessarily scientifically trained, may favour policies with limited scientific backing to obtain public support. We illustrate these tensions with two case studies where the scientific consensus went up against the governing parties' chosen policy. What mechanisms exist to keep the weight of scientific evidence at the forefront of decision-making at the highest levels of government? In this paper, we propose that Canada create "Departmental Chief Science Advisors" (DCSAs), based on a program in the UK, to help complement and extend the reach of the newly created Chief Science Advisor position. DCSAs would provide advice to ministers and senior civil servants, critically evaluate scientific work in their host department, and provide public outreach for the department's science. We show how the DCSAs could be integrated into their departments and illustrate their potential benefits to the policy making process and the scientific community.